Opposite effects of anxiety and depressive symptoms on executive function: The case of selecting among competing options - Snyder, Hannah R. (2013)
People constantly face the need to choose one option from among many, such as when selecting words to express a thought. Selecting between many options can be difficult for anyone, and can feel overwhelming for individuals with elevated anxiety. The current study demonstrates that anxiety is associated with impaired selection across three different verbal tasks, and tests the specificity of this finding to anxiety. Anxiety and depression frequently co-occur; thus, it might be assumed that they would demonstrate similar associations with selection, although they also have distinct profiles of symptoms, neuroanatomy, and neurochemistry. Here, we report for the first time that anxiety and depressive symptoms counterintuitively have opposite effects on selection among competing options. Specifically, whereas anxiety symptoms are associated with impairments in verbal selection, depressive symptoms are associated with better selection performance. Implications for understanding the mechanisms of anxiety, depression, and selection are discussed.